People's Republic of China : Detailed Assessment Report: IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses a detailed assessment report on the observance of China's compliance with the International Organization of Securities Commission's objectives and principles of securities regulation. The reform of nontradable shares introduced a market-based pricing system for so-called nontradable shares in listed companies closely held by government and semigovernment authorities. The China Securities Regulatory Commission has the ability to share public and nonpublic information with both domestic and foreign counterparts without other external process, for the purpose of performing regulatory and supervisory functions.